Traditional pottery in a modern guise: an investment that combines authenticity and innovation (The International Journal of Educational Sciences and Arts, 2025)
The research summarizes the vision of the wonderful ceramic heritage within a framework through economic investment that combines wonderful authenticity, as the research problem helps through planning the following question: How can the ceramic craft be obtained as a source of income and an investment field with an analysis of the challenges facing potters, then we seek to search for a center towards studying the ceramic craft as a source of income and an investment field, Analyzing the challenges facing potters in transforming their craft into a source of income, and presenting practical mechanisms for marketing ceramic products locally and internationally. The importance of the research lies in its connection between the heritage and artistic dimensions of ceramics and their economic developmental dimensions. It also serves potters by investing in their talents and transforming them into economic projects, Supporting development initiatives that seek to promote small and medium-sized ceramic industries, highlighting the most important challenges facing potters in transforming the ceramic craft into a source of income, and clarifying practical mechanisms for marketing ceramic products locally and internationally, The research results showed that transforming the pottery craft into an investment and source of income requires concerted efforts between potters, cultural institutions, and government agencies, and considering and promoting e-commerce as a primary means of marketing pottery, Potters must focus on innovation in their designs and products while preserving authenticity and heritage identity, and exploit the craft of pottery to make it an important area of ​​economic development for potters and society itself by integrating the ceramic products industry into economic development plans.
Keywords: Heritage Pottery; Investing in Pottery; Pottery Marketing; Authenticity and Innovation